Additional observations on the gross morphology and microstructure of Baccaconularia Hughes, Gunderson et Weedon, 2000, a Cambrian (Furongian) conulariid from the north-central USA - Van Iten, Heyo; Leme, Juliana de Moraes; Simões, Marcello Guimarães [UNESP] (Elsevier, 2006)
Baccaconularia Hughes, Gunderson et Weedon, 2000, from the Furongian Series (Cambrian System) of the north-central USA, has been interpreted as a conulariid cnidarian, based on a suite of gross morphological similarities shared only with other post-Cambrian genera currently assigned to this group. Closely spaced, squarish to subrectangular facial nodes of Baccaconularia are aligned in distinct longitudinal files. Nodes also display a subtler, more or less rectilinear transverse alignment, though this pattern commonly is disrupted by offset parallel to the longitudinal files. In their shape and pattern of arrangement, the nodes of Baccaconularia are most similar to the squarish to elongate nodes of Pseudoconularia Bouček, 1939. Longitudinal node files of Baccaconularia may also be compared with the longitudinal facial ridges of Conularia cambria Walcott, 1890 from the Furongian of Wisconsin. Apical angles of Baccaconularia range from approximately 13° to 14.5°. Scanning electron imaging of B. cf. robinsoni shows that its thin, phosphatic skeleton is finely lamellar, with the thickness of individual lamellae measuring approximately 1 μm. The skeleton also exhibits microscopic circular pores and crater-like pits that range from approximately 5 to 10 μm in diameter. These pores and pits are similar in size, geometry, areal density and pattern of arrangement to those of many post-Cambrian conulariids. Microscopic circular pores are documented here for the first time in the genus Archaeoconularia Bouček, 1939 from the Upper Ordovician of the Czech Republic. Although the origin of the pores and pits is open to alternative interpretations, the discovery of these features and fine lamination in Baccaconularia strengthens the argument that this genus is a Cambrian conulariid. © 2006 Nanjing Institute of Geology and Palaeontology, CAS.
Keywords: Cambrian; Circonulariids; Conulariids; Microbioclaustrations; Microborings; Microstructure; invertebrate; microstructure; morphology; Ordovician; scanning electron microscopy; skeleton; taxonomy; ultrastructure; Central Europe; Czech Republic; Eurasia; Europe; North America; United States; Wisconsin; Conulariida